2021
DOI: 10.1080/14763141.2020.1849379
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic and kinematic comparison of the two-footed and step-out back handsprings on the balance beam

Abstract: The back handspring is one of the most commonly performed skills on the balance beam in women's gymnastics. Despite this, quantitative research on the beam has often been overlooked. This study aimed to investigate the kinetic and kinematic variables during the performance of two back handspring techniques on the beam: the back handspring with two footed landing and the back handspring step-out. A modified balance beam was fixed to a force plate with an isolated mat for landing to allow analysis of the take-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Jump-offs from the beam are executed with one foot behind the other, and the run-up speed is reduced due to the limited run-up distance and the high requirements on dynamic balance during the run-up. These factors may reduce the effectivity of the jump-off [ 40 ]. Nevertheless, the slightly offset foot position at jump-off seems to provoke a jump-off that is mainly dependent on the level of single-leg peak power.…”
Section: Discussionmentioning
confidence: 99%
“…Jump-offs from the beam are executed with one foot behind the other, and the run-up speed is reduced due to the limited run-up distance and the high requirements on dynamic balance during the run-up. These factors may reduce the effectivity of the jump-off [ 40 ]. Nevertheless, the slightly offset foot position at jump-off seems to provoke a jump-off that is mainly dependent on the level of single-leg peak power.…”
Section: Discussionmentioning
confidence: 99%
“…He concluded that the most appropriate wrist joint angle during the support phase was 95 degrees and that the wrist joint angle was influenced by aspects such as the number of years of training and shoulder joint angle. Science and technology are assisting human development, and along with the continuous progress of scientific research methods, kinesiology research methods have developed from two-dimensional planar analysis to three-dimensional analysis techniques, and with the continuous development and enhancement of research methods, more diversified data analysis is put into the research of different projects [12]- [14].…”
Section: Introductionmentioning
confidence: 99%